Therapeutic potential of PDA@MT in mitigating oxidative stress in obstructive sleep apnea based on biomedical images - Zeming Zhang; Wenhui Wang; Li Wei; Li Han; Zaiyan Wang; Hao Chen (SLAS Technology)
Obstructive sleep apnea (OSA) is a common sleep disorder that affects breathing and is accompanied by increased oxidative stress, leading to multiple health problems. This study evaluated the therapeutic efficacy of PDA@MT on oxidative stress and OSA model, providing new ideas for the treatment of OSA. Firstly, PDA@MT nanoparticles were synthesized and their embedding efficiency and drug loading capacity were evaluated. The physicochemical properties of the particles were analyzed by means of particle size and ζ potential test, transmission electron microscope (TEM) imaging and sample stability test. Subsequently, cell viability assay, cell uptake assay and antioxidant assay were performed to evaluate the therapeutic effect of nanoparticles in vitro. OSA rat models were established, and histological analysis, immunofluorescence detection and reactive oxygen species (ROS) detection were performed to evaluate the efficacy of PDA@MT in vivo, and finally statistical analysis was performed. PDA@MT nanoparticles showed good cytocompatibility and significant antioxidant capacity, and could effectively reduce ROS levels in vitro. Multiple validated evaluations have shown that PDA@MT significantly improves respiratory status in model rats in OSA models, showing promising therapeutic potential. Biosafety evaluation results showed that PDA@MT is safe for use in vivo. Medical thermal images play a key role in evaluating the therapeutic effect of the nanoparticles and provide an important basis for further research and development.